Competência em informação e aprendizagem no contexto arquivístico - MARQUES, Ariadne Pinto (2023)
This work is directed to the relation between Information Literacy and learning in the archival context, with emphasis on the role of the University as a social instrument. The objective was to map the academic-scientific production around the theme using the Systematic Bibliographic Review, described as a set of procedures divided into three phases: Input, Processing and Output. In the initial protocol for the development of the research, it was decided that it would be done on the Portal de Periódicos da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), within the thematic area, in Spanish, following the search strings elaborated from the identified keywords. The results obtained indicated a low bibliographic production around the themes discussed. Sinde such results provided reflections such as the need for information literacy in higher education precisely in the teaching of Archival Science thus having its insertion in the archivist’s performance in an intrinsic way mainly due to the technological environment in which we live, where obtaining information flows quickly, requiring autonomy to know how to deal ethically in accessing, retrieving and organizing information, added to other skills relevant to the profile of the contemporary archivist.